Factors that influence international nursing students' experiences and perceptions of their learning environments: a scoping review protocol. Issue 11 (26th November 2021) - Tallon, Mary; Brown, Janie; Solomons, Terena; Kalembo, Fatch; Bosco, Anna; Lim, Eric; Ngune, Irene; Moore, Kate; Wilson, Sally
ABSTRACT: Objective: The objective of this review is to explore the research on factors that influence international undergraduate nursing students' experiences and perceptions of their learning environment. Introduction: International nursing students bring valuable cultural and economic opportunities to universities and health care. It is important that their clinical learning experiences are positive. Factors that influence nursing students' experiences may include cultural and communication differences, diversity related to health care systems, learning and teaching strategies, and programs to improve communication. International nursing students' experiences and perceptions are reported in terms of expressed confidence, perceived competence, and levels of satisfaction. A scoping review is required to identify what is known and to identify the knowledge gaps in this area. Inclusion criteria: International nursing students are those who are enrolled in an undergraduate nursing program in a higher-education institution in a country other than their own. International students studying vocational nursing and exchange students will be excluded. The learning environment is considered to be one in which any person who may influence patient care learns. Primary research, both qualitative and quantitative methods, published since 1995 in any language that the research team can translate will be included. Methods: This review follows the JBI methodology for scoping reviews. Data extraction will include the factors influencing students' experiences and the concepts that were explored. Data analysis will include frequencies of concepts and associations between them. Results will be presented in tabular form and mind maps. Scoping review registration number: Open Science Framework (osf.io/r4v6q)